The Products of Aziz Gardi and their Reflect Ions in Academic Research: for Example, Doctoral thesis of the Kurdish Literature Field of the University of Salahaddin (1996-2023) - Pshtiwan Asaad Kareem; Shakawan Farhad Mohammed (Zanco Journal of Humanity Sciences)
Scientific production and its  reuse as a source in other scientific works are important and  valuable. The products and scientific works of Dr. Aziz Gardi have their own values and significance in the Kurdish library, andas the source is based on and depends on in the academic research process. From this point on، we have given the title of the research as: "The products of Aziz Gardi and their reflectionsin academic research. For exampledoctoral thesis of the Kurdish literature field of the University of Salah al-Din (1996-2023), in order to show the balance of his works and products. Moreover, the scope of this research is withinthe framework of the doctoral thesis in the field of literature at the University of Salah al-Din/ Erbil, and they were taken as examples between 1996 and 2023. The main task of this research is to show and identify Aziz Gardi’s products such as books, writings, researches (master’s and doctoral thesis), preparation and explanation, translation and its reflection in academic letters. Furthermore, this research would have answer to these questions: How did the products reflect? What products were used and which one had been used the most? Which pages were most used? And what are the rates? To do the task correctly and issue the rate, Descriptive-Statistical method has been followed.